MELESTARIKAN KEARIFAN BUDAYA LOKAL MELALUI PERMAINAN TRADISIONAL ULAR TANGGA - Suananda, I Kadek Hadi; Prima Dewi PF, Kadek Aria (Institut Hindu Dharma Negeri Denpasar, 2018)
This article aims to illustrate the application of traditional snake ladder games in the learning process to preserve local cultural wisdom. This is motivated by the phenomenon of current student activity changes, which more often play modern games that are identical with the use of technology such as video games and online games. As a result, the traditional student games are beginning to be forgotten and become alien among the students. In addition, the level of addiction to the modern game on the students is also high so it affects the habits and behavior of students. As a cultural heritage containing noble values, the traditional game should be preserved And maintained its existence by introducing traditional games through the process of learning in the classroom. One of the traditional games that can be applied in the process of learning in the classroom is a snake ladder game. In this article the method used is the method of observation. Based on the observation results obtained that the traditional games can stimulate students in developing cooperation in groups in the learning process, , Interact as positively, can condition students in self-control, develop empathy for friends, obey the rules, and appreciate others. Thus, it is understood that traditional games can have an excellent impact in helping to develop students' emotional and social skills.